Misdiagnosis of Total Parental Nutrition-Related Riboflavin Deficiency: Three Case Reports of Diagnostic Error - Grant J. Shafer; Jose E. Abdenur; Vijay Dhar; Michel Mikhael (Thieme Medical Publishers, Inc., 2023)
Total parental nutrition (TPN) is a critical component of neonatal intensive care. Supply shortages leading to deficiencies in TPN constituents can have devastating consequences for critically ill patients in the neonatal intensive care unit (NICU), who may be initially misdiagnosed as potential inborn errors of metabolism. Here, we present three cases of patients with prolonged TPN dependence due to intra-abdominal pathology who presented with signs and symptoms concerning for metabolic disorders and who were ultimately determined to be a result of vitamin deficiencies in the TPN after unnecessary testing and interventions had occurred. These diagnostic errors highlight the need for clinicians to maintain a high index of suspicion for nutritional deficiencies when treating patients in the NICU with potential metabolic disorders during times when TPN constituents are not available, as well as advocating to ensure that adequate supplies are maintained for this vulnerable population.